Qard Al-Hasan Funds as Islamic Social Finance Mode: Analytical Study of Islamic Banks of Yemen - Al-Melahi, Abdellah Ali Ahmed; Adam Sa'ad, Auwal; Othman, Anwar Hasan Abdullah (IIUM Press, 2021)
This study aims to review and discuss the Qard al-hasan in Islamic banks in Yemen. The study also discusses the challenges that face Qard al-hasan product. It follows series of approaches to achieve the objectives of the study. It uses a descriptive approach to study the element of the subject. It also uses the analytical approach to analyze annual financial and social responsibility reports that issued by the largest Islamic banks and compares them. T he comparative approach was also used when comparing between Islamic banks in granting Qard al-hasan amount. The study finds that Islamic banks can finance by Qard al-hasan. The study also finds the percentage of Qard al-hasan application is different from one bank to another. The study concludes that Qard al-hasan product did not include the social responsibility reports as Islamic social finance mode. Moreover, The Islamic banks in Yemen do not infinitive publish and special reports on the number of clients or the purpose of the financing of Qard al-hasan. The study concludes with a number of recommendations including the need to activate Qard al-hasan product, show it as socially responsible, and finance it by several sources. The study also recommends that the supervisory authorities to legislate policies and procedures related to the Qard al-hasan product with cooperation with Islamic banks and relevant authorities.